Variation of Volleyball Basic Technique Through Games Approach - Risma, Siti Ayu; Dlis, Firmansyah; Samsudin, Samsudin (Department of Physical Education, Sport, Health and Recreation, 2020)
The study aimed to develop volleyball basic technique using games approach. The game help students to create a sport is more interesting. A study used to research and development using Borg and Gall method. There are ten steps in research. Process of collecting data used observation, interview, test, and questionnaire. Data analysis used peer assessment and judgment expert. The study conducted in Junior High School Palembang. The results of the findings show that the basic technique of volleyball consists of 6 types namely passing down, passing up, service down, service up, volleyball block, and smash. Each type of basic technique taught has different variations of the game which are oriented to the needs and characteristics of volleyball. The results of the study have implications for changes in the concept of learning sports, especially volleyball.